Types of Directive Speech Acts in the Translation of Surah An-nisa’ - Daulay, Pengabdi; Setia, Eddy; Lubis, Tasnim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The objective of this study was to classify the type of directive speech in Surah An-Nisa translation. The definition and meaning of the directive speech act by Searle (1979) was applied in this study to identify the directive speech in Surah An-Nisa’ translation. The data source was the text of Al-Quran Mushaf Utsmani with its translation in Bahasa Indonesia from the Ministry of Religion of Indonesia. The qualitative method was applied in this study. The data of this research were utterances originating from the text of the Al-Quran and their translation. The directive speech acts in Surah An-Nisa' consists of 176 verses as the object of study. The data collection technique used was document study. The data were analyzed by using Miles Huberman data analysis. The study results showed that there were six types of directive speech acts in Surah An-Nisa’. They were (1) directive speech acts of commanding, (2) prohibiting, (3) advises, (4) asking, (5) persuading, and (6) allowing.